Efek Hepatotoksisitas Tanaman Obat - Fatti, Vally T. T.; Lintong, Poppy M.; Sambuaga, Maria K. (Universitas Sam Ratulangi, 2021)
Abstract: The utilization of medicinal plants in Indonesia has been going on for generations even before modern medicine began to be marketed. Although its properties are widely known, but certain medicinal plants can give toxic effects to the liver. This study was aimed to re-evaluate the hepatotoxic effects of medicinal plants and changes in liver morphology. This was a literature review study using databases of Pubmed, ClinicalKey, and Google Scholar. The results obtained five medicinal plants that had hepatotoxic effects. Areca catechu showed morphological changes in the form of hemorrhagic, sinusoid dilation, lobular inflammation, lobular disarray, necrosis, interface hepatitis, microsteatosis, hepatocellular cholestasis, and steatosis. Myrmecodia pendans showed the presence of fat degeneration, necrosis, and inflammatory cell infiltration. Annona muricata indicated the presence of hepatocyte swelling. Gynura divaricata showed increases of SGOT and SGPT levels. Vernonia amygdalina Del showed the presence of cellular degeneration and necrosis of hepatocytes. In conclusion, the most diverse morphological changes of liver are caused by Areca catechu along with large dose consumption meanwhile the most minimal morphological changes of the liver are caused by Annona muricata.Keywords: herbal medicine; hepatotoxic effectÂ Â Abstrak: Pemanfaatan tanaman obat di Indonesia telah berlangsung selama turun-temurun bahkan sebelum obat modern mulai dipasarkan. Meskipun khasiatnya telah banyak diketahui, namun tanaman obat tertentu dapat memberikan efek toksik pada hati. Penelitian ini bertujuan untuk mengevaluasi kembali efek hepatotoksik tanaman obat dan perubahan morfologik hati. Jenis penelitian ialah literature review, menggunakan database Pubmed, ClinicalKey, dan Google Scholar. Hasil penelitian ini mendapatkan lima jenis tanaman obat yang bersifat hepatotoksik. Areca catechu menunjukkan adanya perubahan morfologik berupa perdarahan, dilatasi sinusoid, inflamasi lobular, lobular disarray, nekrosis, interface hepatitis, mikrosteatosis, kolestasis hepatoseluler, dan steatosis. Myrmecodia pendans menunjukkan adanya degenerasi lemak, nekrosis, dan infiltrasi sel radang. Annona muricata menunjukkan adanya pembengkakan hepatosit. Gynura divaricata menunjukkan adanya peningkatan kadar SGOT dan SGPT. Vernonia amygdalina Del menunjukkan adanya degenerasi dan nekrosis hepatosit. Simpulan penelitian ini ialah perubahan morfologik hati yang paling beragam disebabkan oleh Areca catechu seiring dengan besar dosis yang dikonsumsi sedangkan perubahan morfologik hati yang paling minimal disebabkan oleh Annona muricata.Kata kunci: tanaman obat; efek hepatotoksik